Effect of sequential vs. simultaneous dual growth dactor release from structured heparin-poly-electrolyte multilayer coatings on peri-implant bone formation and angiogenesis in pig mandibles - Kauffmann, Philipp; Wolfer, Susanne; Behrens, Christina; Schlosser, Pauline; Dullin, Christian; Schirmer, Uwe; Liefeith, Klaus; Schliephake, Henning (Journal of Functional Biomaterials, 2025)
The aim of the present study was to test the sequential and simultaneous release of rhBMP2 and rhVEGF165 from poly-l-lysine-heparin (PLL-Hep) poly-electrolyte multilayer (PEM) coating on titanium surfaces for their ability to enhance peri-implant bone formation and CD31 expression around disc-shaped titanium implants (5 × 7 mm) in mini-pig mandibles. Bare titanium surfaces loaded with respective growth factor combinations served as controls. Ten different surface conditions were tested exhibiting early VEGF release, early BMP release, simultaneous VEGF and BMP release, and sole VEGF/BMP release, respectively. The implants were inserted press-fit into 5 mm trephine cavities at the lower border of the mandibles of mini-pigs and left to heal for 4 and 13 weeks. After 4 weeks, there was no significant difference in peri-implant bone formation, bone-implant contact nor CD31 expression between the different surface conditions. After 13 weeks, bone formation was significantly higher in the zone of 100 μm next to implant surfaces releasing either BMP alone or with an early release of BMP2. Expression of CD31 has significantly decreased from 4 to 13 weeks with significantly higher values in the group of implants with early release of BMP2. The results indicate that the range of released growth factors is limited to a distance of approximately 100 μm and that the sequence of early release of BMP2 followed by VEGF165 promotes peri-implant bone formation and peri-implant angiogenesis, which is in contrast to the current understanding of the temporal patterns of growth factor release for enhancement of bone formation.